LANGUAGE LEARNING STRATEGIES OF ESP LEARNERS: A COMPARISON BETWEEN DURING AND POST-PANDEMIC SITUATION - Febriyanti, Emma Rosana (Universitas Muhammadiyah Metro, 2023)
Several studies have highlighted the importance of language learning strategies (LLS) for second and foreign-language learners. These strategies have played a significant role in distinguishing between more successful and less successful language learners. However, the outbreak of the COVID-19 pandemic in 2020 brought about unprecedented changes in the teaching-learning process, with a shift towards online platforms. This study aimed to determine what language learning strategies were applied by the 85 learners of the Mathematics and Biology Departments, ESP (English for Specific Purposes) learners taking English courses during and after the pandemic. In addition, this study also investigated whether there are any similarities or differences in the language learning strategies employed by using comparative design. To collect data, the researcher utilized the Strategy Inventory of Language Learning from Oxford (1990), translated into Indonesian, to ensure clear comprehension among the learners. Descriptive statistics for means and standard deviations were then used to analyze the data. The analysis revealed that, regardless of the circumstances, the students applied all strategies in their learning. Then, they consistently applied the metacognitive and memory strategies more frequently than others.Additionally, the findings indicated that the students utilized the social strategy during the COVID-19 pandemic, while the affective strategy was employed somewhat in the post-pandemic period. The outcomes of this study have significant implications as they raise awareness among learners and ESP instructors about the benefits of employing language learning strategies. Recognizing and utilizing these strategies can significantly enhance language learning outcomes. By understanding the preferred strategies employed by students during different periods, instructors can tailor their teaching approaches accordingly to maximize the effectiveness of language instruction.